2021
DOI: 10.1039/d0sc06364a
|View full text |Cite
|
Sign up to set email alerts
|

Using internal electrostatic fields to manipulate the valence manifolds of copper complexes

Abstract: Secondary coordination sphere electrostatic effects tune the valence manifolds of copper centers, impacting molecular geometries, photophysical properties, and redox potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“… [16] Just recently, Tomson and co‐workers suggested that electrostatic interactions with the d(z 2 )‐orbital might be important for the metal–N(anchor) distance in copper(I) complexes. [17] Our computational analysis (see below) suggests that repulsive electrostatic interactions and negative hyperconjugation cause this structural feature.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“… [16] Just recently, Tomson and co‐workers suggested that electrostatic interactions with the d(z 2 )‐orbital might be important for the metal–N(anchor) distance in copper(I) complexes. [17] Our computational analysis (see below) suggests that repulsive electrostatic interactions and negative hyperconjugation cause this structural feature.…”
Section: Resultsmentioning
confidence: 83%
“…This corroborates a formal oxidation state of +IV for the cobalt ion in 4 and suggests a reduced repulsive interaction with the N anchor of the ligand (cf. Figures S63–S68), thus, reducing the Co−N distance in analogy to the previously studied copper complexes [17] and attenuating the p(z)‐character of the nitrogen atom's lone pair of electrons (e.g. TPSSh: 3 , Σ(C−N−C)=358.8°; 4 , Σ(C−N−C)=351.9°).…”
Section: Resultsmentioning
confidence: 89%
“…[16] Just recently,T omson and coworkers suggested that electrostatic interactions with the d(z 2 )-orbital might be important for the metal-N(anchor) distance in copper(I) complexes. [17] Our computational analysis (see below) suggests that repulsive electrostatic interactions and negative hyperconjugation cause this structural feature.…”
Section: Resultsmentioning
confidence: 83%
“…This corroborates aformal oxidation state of + IV for the cobalt ion in 4 and suggests ar educed repulsive interaction with the Nanchor of the ligand (cf. Figures S63-S68), thus,r educing the Co À Nd istance in analogy to the previously studied copper complexes [17] and attenuating the p(z)-character of the nitrogen atomsl one pair of electrons (e.g.TPSSh: 3, S(CÀNÀC) = 358.88 8; 4, S(CÀ NÀC) = 351.98 8). Concomitantly,t he covalencyo ft he pinteraction between the metalsd(xz)-and d(yz)-orbitals with the imido ligand is further enhanced, with each having about 50 %c ontribution.…”
Section: Angewandte Chemiementioning
confidence: 76%
“…98 In more recent work, Tomson observed shifts in redox potentials that were attributed to stabilization of a dz 2 orbital, and supported this idea with DFT calculations. 99 Redox potentials were primarily used to probe cation effects in these examples, but incorporation of iron in our complexes enabled us to use Mössbauer spectra that can be directly related to the electronic structure of iron. Through the combination of spectroscopy and DFT, we identified cation-dependent changes in orbital energetics.…”
mentioning
confidence: 99%